Colonialism, Resistance, and Environmental Issues in James Cameron’s Avatar (2009) - Yosua Tunas Wicaksono; Daniel Ginting; F.X. Dono Sunardi (INTERACTION: Jurnal Pendidikan Bahasa, 2023)
Avatar has revolutionized the film industry. James Cameron introduced a new level of immersive visual storytelling that captivated audiences worldwide. While some previous studies on Avatar have highlighted some important research findings, they seem to leave Avatar’s themes understudied. "Avatar" explores themes of colonialism, resistance, and environmental issues, highlighting the harm caused by resource exploitation and the need for responsible resource management. It depicts the exploitation of weaker groups by more powerful ones, with humans representing the colonizers and the Na'Vi people representing the colonized. The film emphasizes the resistance of the Na'Vi, their fight to defend their homes, and the involvement of nature in the war against humans. Additionally, it addresses environmental destruction caused by human greed and disregard for the environment. This study suggests that further research could explore comparative analysis with other works to provide a broader understanding of the themes.